1992
DOI: 10.1099/00221287-138-4-709
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and partial sequencing of the proteinase gene complex from Lactococcus lactis subsp. lactis UC317

Abstract: The proteinase genes from Lactococcus factis subsp. factis UC317 were identified on a plasmid, pCI310, which is a deletion derivative of a cointegrate between pCI301, the 75 kb Lac Prt plasmid from UC317 and the 38.5 kb cryptic plasmid from that strain. The prt genes were cloned using a replacement cloning strategy whereby fragments from pCI310 were exchanged with the equivalent fragments in pNZ521, which contains the cloned proteinase genes from L. factis subsp. factis SK112. This generated two plasmids which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Recently two other lactococcal strains, namely L. lactis subsp, lactis NCDO763 (which should possibly be reclassified as a cremoris strain) and L. lactis subsp, lactis UC317, were also shown to have proteinases with an intermediate specificity pattern. The proteinases from these two strains cleaved /3-casein in a manner similar to that of the Pl-type proteinase from the strain Wg2 but were also able to hydrolyse C~l-casein [25,63]. Analysis of the proteinase genes of these two strains [35,63] revealed that the nucleotide sequence was indeed intermediate between the nucleotide sequences of the P, lrstrain SKl l and the Pj-strain Wg2 proteinase genes with respect to the seven amino acid residues believed to be responsible for the specificity differences between the two proteinase types.…”
Section: Cleaved Bondmentioning
confidence: 89%
See 1 more Smart Citation
“…Recently two other lactococcal strains, namely L. lactis subsp, lactis NCDO763 (which should possibly be reclassified as a cremoris strain) and L. lactis subsp, lactis UC317, were also shown to have proteinases with an intermediate specificity pattern. The proteinases from these two strains cleaved /3-casein in a manner similar to that of the Pl-type proteinase from the strain Wg2 but were also able to hydrolyse C~l-casein [25,63]. Analysis of the proteinase genes of these two strains [35,63] revealed that the nucleotide sequence was indeed intermediate between the nucleotide sequences of the P, lrstrain SKl l and the Pj-strain Wg2 proteinase genes with respect to the seven amino acid residues believed to be responsible for the specificity differences between the two proteinase types.…”
Section: Cleaved Bondmentioning
confidence: 89%
“…The proteinases from these two strains cleaved /3-casein in a manner similar to that of the Pl-type proteinase from the strain Wg2 but were also able to hydrolyse C~l-casein [25,63]. Analysis of the proteinase genes of these two strains [35,63] revealed that the nucleotide sequence was indeed intermediate between the nucleotide sequences of the P, lrstrain SKl l and the Pj-strain Wg2 proteinase genes with respect to the seven amino acid residues believed to be responsible for the specificity differences between the two proteinase types. The action of one of these enzymes (from strain NCDO763) has been studied in considerable detail with respect to its action on /3-casein [19,21,25] and on ~-, ~z-and K-casein [25].…”
Section: Cleaved Bondmentioning
confidence: 89%
“…The Bacillus subtilis proteinase negative deletion mutant, DB104 (Kawamura and Doi 1984), was used as recipient in transformation experiments using pGKV210npr, which carries the B. subtilis neutral proteinase gene (van de Guchte et al 1989) and pCI3601 carrying the Lactococcus lactis UC317 proteinase genes (Law et al 1992). The protocol for development of competence and transformation has been described previously (Kunst et al 1994).…”
Section: Transformation Of Bacillus Subtilismentioning
confidence: 99%
“…An increase in proteolytic activity of five-fold was reported. In both studies Law et al, 1992), no or only minor effects of the increased proteinase production on growth rate and rate of acid formation were observed. The proteolytic activity of a strain carrying approximately eight copies of the proteinase genes on the chromosome was eleven times higher than that of a strain carrying only two copies of the prt genes .…”
Section: Engineering Of the Proteinase Prtpmentioning
confidence: 79%